Phylogenetic analysis of nematode nuclear 18S rDNA sequences indicates the genus Tripylina Brzeski, 1963 (Nematoda: Tripylidae de Man, 1876) should be placed in Enoplida - Zhao, Zeng Qi; Buckley, Thomas R. (Zootaxa, 2009)
We have made an extensive study of New Zealand representatives of nematodes from the family Tripylidae de Man, 1876. Based on SSU DNA sequence data and phylogenetic analysis, the genera Tripylina Brzeski, 1964 and Trischistoma Cobb, 1913 are not closely related to Tripyla Bastian, 1865, the type genus of the family Tripylidae de Man 1876. The genus Tripylina is sister to Trischistoma and Trefusia de Man, 1893 and is more closely related to Enoplida than to Triplonchida. Our phylogenetic results indicate that Tripylina should be placed in Enoplida.